Penguatan Literasi Lingkungan Desa Kubang Utara Sikabu melalui Sosialisasi dan Inovasi Pengelolaan Sampah - Sandra Dewi; Aliza Novia Rahmawati; Miftahurrahmi Oktavia; Nisfi Rahmadhani; Agrina Riandani (CV. ITTC INDONESIA, 2025)
Plastic waste that is difficult to decompose is a serious problem in preserving the environment, especially in rural areas such as Kubang Utara Sikabu Village. The lack of waste management facilities and infrastructure as well as the low level of community awareness further exacerbates the condition. Through the 2025 work program of Universitas Negeri Padang's Community Service Program (KKN), an environmental literacy strategy was carried out that included socialization of waste management, training in ecobricking, and installing educational information boards about the length of time inorganic waste decomposes. The goal of this program is to increase community understanding and participation in waste management through the ecobrick method. The information boards installed in each hamlet can be an educational medium that can shape the environmental awareness of the community. This program encourages community awareness and behavior change towards a more environmentally friendly lifestyle.